Contemplating the Majesty of Lailatul Qadr Through the Stylistic Patterns of Surah Al-Qadr - Ikroma, Aula; Lu'lu', Habibah Khair; Dewi, Salwa Anggita (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Surah Al-Qadr is one of the short chapters in the Qur’an that emphasizes the majesty of Lailatul Qadr. This night, as mentioned in the surah, is believed to be a blessed night whose value surpasses that of a thousand months. This study aims to uncover the profound meaning of the greatness of Lailatul Qadr through a stylistic analysis of the surah. The research employs a qualitative descriptive method with an Arabic stylistic approach. The primary source of this study is Surah Al-Qadr, while the secondary sources include various articles related to Arabic stylistics and analyses of Surah Al-Qadr.Data analysis was conducted through stages of collection, selection, and in-depth examination. The findings show that the linguistic aspects of Surah Al-Qadr successfully reveal its grandeur and spiritual depth as a night full of blessings. In terms of phonology, the use of sound repetition evokes a sacred atmosphere and deepens the spiritual impression. Morphologically, the selection of deeply meaningful words creates a strong depiction of the night’s magnificence. Semantically, the phrase “better than a thousand months” carries symbolic significance.The conclusion of this study affirms that the stylistic features of Surah Al-Qadr not only enrich the linguistic beauty of the Qur’an but also serve as a means to reflect upon and understand its divine messages.